Struktur Modal dan Nilai Perusahaan Serta Dampak Mediasi Profitabilitas Perusahaan Makanan dan Minuman Indonesia 2020-2022 - Deva Adalia; Y. Djoko Sukoco (Jurnal Bisnis Inovatif dan Digital, 2024)
This research seeks to examine the influence of capital structure on the valuation of food and beverage companies within the sub-sector that are listed on the Indonesia Stock Exchange during the time frame of 2020-2022, with the inclusion of profitability as a mediating factor. Employing a quantitative approach, the study utilizes a purposive sampling method to select 29 samples from a population of 42 food and beverage companies listed on the Indonesia Stock Exchange. The analysis of hypotheses is conducted through simple linear regression, multiple linear regression, and the sable test. The results of the study indicate that capital structure positively impacts profitability, influences company value in a negative manner, profitability does not directly affect company value, and profitability does not act as a mediator in the relationship between capital structure and company value.